2021
DOI: 10.21203/rs.3.rs-255153/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring Traditional Veterinary Practices from Gujjar and Bakarwal Tribes of District Poonch, Jammu & Kashmir: A Boon for Animals from Our Ancestors

Abstract: Background: Gujjar and Bakarwal tribal communities are a treasure trove of traditional veterinary knowledge as they have been using plants to keep their livestock healthy and free from diseases. However, this knowledge is getting diminished day by day due to several factors. The present study was aimed to survey and document the medicinal plants used traditionally by the tribal communities of Gujjar and Bakarwal in the Poonch district of Jammu and Kashmir (J&K), India to treat various livestock ailments.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Species like sheep, goat and cow are used for milk and often meat, at the same time these species are sold for money. Dutta et al (2021) also reported the dependence of Bakarwal on livestock and lack of modern conveniences. In Jammu and Kashmir, this tribe migrates seasonally from Jammu province to Kashmir and vice versa to avoid unavailability of feed and to protect from the harsh climate.…”
Section: Species and Usage With Respect To Bakarwalmentioning
confidence: 99%
See 1 more Smart Citation
“…Species like sheep, goat and cow are used for milk and often meat, at the same time these species are sold for money. Dutta et al (2021) also reported the dependence of Bakarwal on livestock and lack of modern conveniences. In Jammu and Kashmir, this tribe migrates seasonally from Jammu province to Kashmir and vice versa to avoid unavailability of feed and to protect from the harsh climate.…”
Section: Species and Usage With Respect To Bakarwalmentioning
confidence: 99%
“…The present study documented only natural feeding sources as commercial feeds are expensive, and the local population believes that the use of natural herbs keeps animal species healthy and protects them from various diseases. Different studies from the Jammu and Kashmir have reported the use of medicinal herbs for the wellbeing of livestock (Dutta et al 2021;Dar et al 2018) For winter, when the vegetation is dormant the farmers make use of hay, dried tree leaves, etc., which are processed in autumn.…”
Section: Feed Habitmentioning
confidence: 99%